2018
DOI: 10.11002/kjfp.2018.25.3.344
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin quantification in a Jeju Dendropanax morbifera Lev. extract by varying different parts, harvest times, and extraction solvents

Abstract: Dendropanax morbifera Leveille (Araliaceae) is an endemic species growing in the south-western part of South Korea that has been used in folk medicine and health functional food. In this study, we investigated an extract of quercetin in Jeju D. morbifera by varying different parts (fruit, sprouts, leaves, sprigs, and branches), harvest times, and extraction solvents. In addition, we aimed to establish a simple and reliable HPLC/UV analytical method to determination of quercetin for the quality control and base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Recently, a report demonstrated that DP contains phenolic compounds, including rutin, chlorogenic acid, (+)-catechin, ferulic acid, myricetin, quercetin, and resveratrol, that have anti-inflammatory effects [15]. In our previous study, we suggested quercetin as a marker compound of D. morbiferus after analyzing plant parts (fruits, sprouts, leaves, sprigs, and branches), harvest times, and extraction solvents for quality control [16]. In another study, we reported that L -arginine and γ-aminobutyric acid (GABA) levels in DP were increased by enzymatic hydrolysis and extraction (producing Hy-DP) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a report demonstrated that DP contains phenolic compounds, including rutin, chlorogenic acid, (+)-catechin, ferulic acid, myricetin, quercetin, and resveratrol, that have anti-inflammatory effects [15]. In our previous study, we suggested quercetin as a marker compound of D. morbiferus after analyzing plant parts (fruits, sprouts, leaves, sprigs, and branches), harvest times, and extraction solvents for quality control [16]. In another study, we reported that L -arginine and γ-aminobutyric acid (GABA) levels in DP were increased by enzymatic hydrolysis and extraction (producing Hy-DP) [17].…”
Section: Introductionmentioning
confidence: 99%
“…DPL was fractionated to n-hexane, chloroform (CHCl 3 ), ethyl acetate (EtOAc), nbutanol (n-BuOH), and water fractions (Supplemental Figure S1). The amounts of chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid, quercetin, and kaempferol in DPL were compared with the high-performance liquid chromatography (HPLC) method according to our previously reported standard method [11,15]. The samples were dissolved in 50% methanol, sonicated for 20 min, and then analyzed using an Agilent 1260 HPLC system (Agilent Technologies, Palo Alto, CA, USA) equipped with an Eclipse XDB-C 18 column (4.6 × 250 mm, 5 µm).…”
Section: Solvent-solvent Fractionation and Hplc Analysis Of Extractsmentioning
confidence: 99%
“…leaf extract (DPL) have various pharmacological properties [8][9][10]. Previously, we proposed the use of quercetin and kaempferol as chemical markers for the quality control of D. morbiferus after analyzing parts, seasons, and extraction methods [11]. Moreover, we reported the antiobesity effect [12] and antihypertensive effect [13,14] of DPL.…”
Section: Introductionmentioning
confidence: 99%
“…Active chemicals in D. morbiferus leaf extract (DP) have also various biological effects [8][9][10][11]. Furthermore, we reported the change in the content of quercetin, a marker chemical, depending on the parts, harvest season, and extraction methods of D. morbiferus for quality control [12]. Quercetin and its metabolites, such as 3-(3-hydroxyphenyl)propionic acid (3HPPA), 3,4-dihydroxyphenylacetic acid (DHPA) and 4-methylcatechol (4MC), administered orally are well known to be able to decrease arterial blood pressure [13][14][15].…”
Section: Introductionmentioning
confidence: 99%